Respuesta :
We are given
Set A: {(5,1), (4,4), (3,9), (2,16), (1,25)}
We can see that for each x value of the set is increasing exponentially.
We can set up a rule for it y = (6-x)^2
y=(6-5)^2 = (1)^2 = 1
y=(6-4)^2 = (2)^2 = 4
y=(6-3) = (3)^2 = 9
y=(6-2)^2 = (4)^2 = 16
y=(6-1)^2 = (5)^2 = 25.
For set B:
Set B: {(1,-5), (2,-3), (3,-1), (4,1), (5,3)}
It's simply linear function as diffrences of y values are constant that is 2.
We can set a rule for it : y = 2x - 7.
y = 2(1) -7 = 2-7 = -5
y = 2(2) -7 = 4-7 = -3
y = 2(3) -7 = 6-7 = 1
y = 2(4) -7 = 8-7 = 1
y = 2(5) -7 = 10-7 = 3.
Answer:
Set A is a quadratic function : [tex]y=x^2-12x+36[/tex]
Set B is a linear function: [tex]y=2x-7[/tex]
Step-by-step explanation:
Here set A : {(1,25), (2,16), (3,9), (4, 4) , (5, 1)}
This is a quadratic function
Let
[tex]y=ax^2+bx+c[/tex]
For (1,25) we get [tex]25=a+b+c[/tex] ....(1)
For (2,16) we get [tex]16=4a+2b+c[/tex] ....(2)
For (3,9) we get [tex]9=9a+3b+c[/tex] ....(3)
Subtracting (1) from (2) we get
[tex]-9=3a+b[/tex] .....(4)
Subtracting (2) from (3) we get
[tex]-7=5a+b[/tex] ....(5)
Subtracting (4) from (5)
[tex]2a=2[/tex]
a=1
Substituting a= 1 in (4), we get
[tex]-9=3(1) + b[/tex]
[tex]b=-12[/tex]
Substituting a = 1 & b = -12 in (1) we get
[tex]c=25-1+12= 36[/tex]
The function is
[tex]y=x^2-12x+36[/tex]
Set B: {(1,-5), (2,-3), (3,-1), (4,1),(5,3)}
This is a linear function
Slope = [tex]\frac{-3+5}{2-1}=2[/tex]
The equation is
[tex]y=2x+c[/tex]
For (1,-5) we get
[tex]-5=2+c[/tex]
[tex]c=-7[/tex]
The equation is
[tex]y=2x-7[/tex]